Observation of Suppressed Charged-Particle Production in Ultrarelativistic Oxygen-Oxygen Collisions - Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Benato,L; Bergauer,T; Dragicevic,M; Giordano,C; Hussain,PS; Jeitler,M; Krammer,N; Li,A; et al. (Physical Review Letters, 2026)
A hot and dense state of nuclear matter, known as the quark-gluon plasma, is created in collisions of ultrarelativistic heavy nuclei. Highly energetic quarks and gluons, collectively referred to as partons, lose energy as they travel through this matter, leading to suppressed production of particles with large transverse momenta ( <a:math xmlns:a="http://www.w3.org/1998/Math/MathML" display="inline"> <a:mrow> <a:msub> <a:mrow> <a:mi>p</a:mi> </a:mrow> <a:mrow> <a:mi mathvariant="normal">T</a:mi> </a:mrow> </a:msub> </a:mrow> </a:math> ). Conversely, high- <d:math xmlns:d="http://www.w3.org/1998/Math/MathML" display="inline"> <d:msub> <d:mi>p</d:mi> <d:mi mathvariant="normal">T</d:mi> </d:msub> </d:math> particle suppression has not been seen in proton-lead collisions, raising questions regarding the minimum system size required to observe parton energy loss. Oxygen-oxygen (OO) collisions examine a region of effective system size that lies between these two extreme cases. The CMS detector at the CERN LHC has been used to quantify charged-particle production in inclusive OO collisions for the first time via measurements of the nuclear modification factor ( <g:math xmlns:g="http://www.w3.org/1998/Math/MathML" display="inline"> <g:msub>